Serotonin synthesis rate and the tryptophan hydroxylase-2: G-703T polymorphism in social anxiety disorder. (October 2016) - Furmark, Tomas; Marteinsdottir, Ina; Frick, Andreas; Heurling, Kerstin; Tillfors, Maria; Appel, Lieuwe; Antoni, Gunnar; Hartvig, Per; Fischer, Håkan; Långström, Bengt; Eriksson, Elias; Fredrikson, Mats
It is disputed whether anxiety disorders, like social anxiety disorder, are characterized by serotonin over- or underactivity. Here, we evaluated whether our recent finding of elevated neural serotonin synthesis rate in patients with social anxiety disorder could be reproduced in a separate cohort, and whether allelic variation in the tryptophan hydroxylase-2 (TPH2) G-703T polymorphism relates to differences in serotonin synthesis assessed with positron emission tomography. Eighteen social anxiety disorder patients and six healthy controls were scanned during 60 minutes in a resting state using positron emission tomography and 5-hydroxy-L-[β - 11 C]tryptophan, [ 11 C]5-HTP, a substrate of the second enzymatic step in serotonin synthesis. Parametric images were generated, using the reference Patlak method, and analysed using Statistical Parametric Mapping (SPM8). Blood samples for genotyping of the TPH2 G-703T polymorphism were obtained from 16 social anxiety disorder patients (T carriers: n =5, GG carriers: n =11). A significantly elevated [ 11 C]5-HTP accumulation rate, indicative of enhanced decarboxylase activity and thereby serotonin synthesis capacity, was detected in social anxiety disorder patients compared with controls in the hippocampus and basal ganglia nuclei and, at a more lenient (uncorrected) statistical threshold, in the amygdala and anterior cingulate cortex. In patients, the serotonin synthesis rate in the amygdala and anterior cingulate cortex was significantly elevated in TPH2 T carriers in comparison with GG homozygotes. Our results support that social anxiety disorder entails an overactive presynaptic serotonergic system that, in turn, seems functionally influenced by the TPH2 G-703T polymorphism in emotionally relevant brain regions.